Harm reduction for smokers living with HIV. Issue 10 (October 2021) - Shuter, Jonathan; Reddy, Krishna P; Hyle, Emily P; Stanton, Cassandra A; Rigotti, Nancy A
Summary: Tobacco use is now a leading cause of death in people living with HIV in the USA. Increasing cessation rates in this group is a public health priority, yet the results of clinical trials aimed at optimising tobacco treatment strategies have been largely disappointing. Combinations of behavioural and pharmacological cessation therapies in people living with HIV have yielded increases in short-term quit rates, but few have shown long-term efficacy. Even with aggressive therapy combining intensive behavioural treatment with pharmacological agents, most smokers living with HIV continue to smoke. The generalised approach to tobacco treatment that prevails in guidelines and in clinical practices might do a disservice to these individuals, who represent a sizable segment of the population of people living with HIV. Harm reduction is a sensible and needed approach for smokers living with HIV who are unable or unwilling to quit. In this Viewpoint, we take an expansive view of harm reduction to include not only cutting down on cigarette intake for persistent smokers, but also reducing smoking's downstream health effects by increasing lung cancer screening and by controlling concurrent cardiovascular risk factors, especially hypertension and hyperlipidaemia.